2011
DOI: 10.1007/s00296-011-2012-x
|View full text |Cite
|
Sign up to set email alerts
|

Local tolerance of intraarticular administration of lornoxicam into the rabbit knee joint

Abstract: The local tolerability of lornoxicam (Xefo) after single and repeated intraarticular administration was assessed in the rabbit and compared to established standard therapies (hyaluronic acid--Synvisc and the glucocorticoid triamcinolone--Triam), and the results are discussed in the context of the literature. Two local tolerance studies were performed using five male rabbits per group. Lornoxicam and competitor products were administered into the right knee joint in a volume of 500 μL. The contralateral left kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…Lornoxicam (LOR) is a non‐steroidal anti‐inflammatory drug (NSAID), with analgesic and anti‐pyretic properties, and although structurally related to piroxicam and tenoxicam, LOR is 10‐fold more potent . Because LOR is used to treat patients with rheumatoid arthritis, osteoarthritis and postoperative management of pain associated with orthopaedic, abdominal and dental surgeries, a rapid onset of action is a desired attribute, but LOR has limited solubility in gastric media which is a rate‐limiting step for rapid absorption .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lornoxicam (LOR) is a non‐steroidal anti‐inflammatory drug (NSAID), with analgesic and anti‐pyretic properties, and although structurally related to piroxicam and tenoxicam, LOR is 10‐fold more potent . Because LOR is used to treat patients with rheumatoid arthritis, osteoarthritis and postoperative management of pain associated with orthopaedic, abdominal and dental surgeries, a rapid onset of action is a desired attribute, but LOR has limited solubility in gastric media which is a rate‐limiting step for rapid absorption .…”
Section: Introductionmentioning
confidence: 99%
“…Lornoxicam (LOR) is a non-steroidal anti-inflammatory drug (NSAID), with analgesic and anti-pyretic properties, 1 and although structurally related to piroxicam and tenoxicam, LOR is 10-fold more potent. 2 Because LOR is used to treat patients with rheumatoid arthritis, osteoarthritis and postoperative management of pain associated with orthopaedic, abdominal and dental surgeries, 1,3,4 a rapid onset of action is a desired attribute, but LOR has limited solubility in gastric media which is a rate-limiting step for rapid absorption. 5 Several techniques have been investigated to enhance the dissolution of poorly soluble compounds, such as micronisation, 6 formation of inclusion complexes with cyclodextrins, 7-9 micellar solubilisation 10,11 and solid dispersions with hydrophilic macromolecules.…”
Section: Introductionmentioning
confidence: 99%
“…Six studies demonstrated no pathological effects of NSAIDs on chondrocytes. 43,47-52 Ekici et al . 48 used dexketoprofen (COX-1 selective NSAIDs) in a rat model.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to that, Shroeder et al . 52 reported that repeated administration (1, 2, or 3 times) of lornoxicam into the knee joint was well-tolerated in rabbits. Using hematoxylin and eosin staining, they reported on mechanical irritation and tract inflammation from the injection and adaptive synoviocyte responses; however, no signs of toxicity to bone or chondrotoxicity were found.…”
Section: Resultsmentioning
confidence: 99%
“…It is difficult to achieve continuous therapeutic effect after intra-articular injection, because a fast and almost complete absorption of Lornoxicam from the joints into the systemic circulation, so it often needs to be repeated several times. 7 Poly (lactide-co-glycolide acid) (PLGA) microspheres are efficient delivery systems for controlled release of low molecular weight drugs, 8 and its drug release considers both drug dissolution and the diffusion of dissolved active principle through the polymeric matrix. 9 PLGA microspheres have been proved to have good therapeutic effect in the treatment of osteoarthritis.…”
Section: Introductionmentioning
confidence: 99%